Perilaku Harian dan Profil Demografi Mempengaruhi Kenaikan Tagihan Listrik Selama Covid-19 di Indonesia: Pendekatan SEM-PLS - Rosyid Al Hakim (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
The Covid-19 pandemic has impacted the use of electrical energy in households. There have been reports of changes in electrical energy consumption before and during the Covid-19 pandemic in several countries. This study aims to review the daily behavior activities and demographic profile of Indonesia's population regarding rising electricity bills during the Covid-19 pandemic through the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. The research method uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. A total of 137 respondents are assumed to have experienced the impact of rising electricity bills during the Covid-19 pandemic in Indonesia. This study proposes four hypotheses to be tested through the SEM-PLS approach. A total of two hypotheses were accepted, and two hypotheses were rejected. Hypothesis H1 (p-value < 0.05) so that H1 is obtained or there is a relationship between daily behavioral activities and increased electricity bills. Hypothesis H3 (p-value < 0.05) so that H3 is accepted or a connection between the respondent's profile and the increase in electricity bills. Meanwhile, additional devices that require electric power and the number of electric pulses purchased have no relationship to the rise in electricity bills during the Covid-19 pandemic in Indonesia.